Career in engineering the art of making useful things - Rogers, Christine; Video Education Australasia (Bendigo, Victoria : Video Education Australasia, 1999)
Using a case study approach, this program explores the opportunities for careers in metal trades-related industries. Areas covered VET, apprenticeships, degrees and corporate training
Title from title screen
Executive producer, Robyn Holdsworth ; editors, Sasha Trikojus, Adrian Vallis ; sound, Joel de Courcy Browne, Tim Mummery ; camera, Tim Mummery, Joel de Courcy Browne, Sasha Trikojus
Narration: Gary Newman
Keywords: Engineering -- Vocational guidance -- Case studies; Career development; Engineers; Engineering